A Fast High Order Iterative Solver for the Electromagnetic Scattering by Open Cavities Filled with the Inhomogeneous Media (Advances in Applied Mathematics and Mechanics, 2013)
The scattering of the open cavity filled with the inhomogeneousmedia is studied. The problem is discretized with a fourth orderfinite difference scheme and the immersed interface method,resulting in a linear system of equations with the high orderaccurate solutions in the whole computational domain. To solve thesystem of equations, we design an efficient iterative solver, whichis based on the fast Fourier transformation, and provides an idealpreconditioner for Krylov subspace method. Numerical experimentsdemonstrate the capability of the proposed fast high order iterativesolver.